2018
DOI: 10.1038/s41598-018-31734-6
|View full text |Cite|
|
Sign up to set email alerts
|

USP4 positively regulates RLR-induced NF-κB activation by targeting TRAF6 for K48-linked deubiquitination and inhibits enterovirus 71 replication

Abstract: Retinoic acid-inducible gene I-like receptor (RLR) is one of the most important pattern recognition receptors of the innate immune system that detects positive and/or negative stranded RNA viruses. Subsequently, it stimulates downstream transcription of interferon regulatory factor 3 (IRF3) and nuclear factor κB (NF-κB) inducing the production of interferons (IFNs) and inflammatory cytokines. Tumour necrosis factor receptor associated factor 6 (TRAF6) is a key protein involved in the RLR-mediated antiviral sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Furthermore, RIG-I-MAVS-TRAF6 signaling induces K63-ubiquitination of Beclin-1, a critical step for inducing autophagy (71). Finally, TRAF6 interacts with Ubiquitin-specific protease 4 (USP4) to induce NF-κB activation following RLR-simulation (72). This is achieved via targeting of TRAF6 for K48-linked deubiquitination.…”
Section: The Role Of Trafs In Rig-i-like Receptor Signalingmentioning
confidence: 99%
“…Furthermore, RIG-I-MAVS-TRAF6 signaling induces K63-ubiquitination of Beclin-1, a critical step for inducing autophagy (71). Finally, TRAF6 interacts with Ubiquitin-specific protease 4 (USP4) to induce NF-κB activation following RLR-simulation (72). This is achieved via targeting of TRAF6 for K48-linked deubiquitination.…”
Section: The Role Of Trafs In Rig-i-like Receptor Signalingmentioning
confidence: 99%
“…Wu et al (2017) showed that PTEN decreased hepatitis C virus replication and the protein phosphatase activity of PTEN is TRAF6 belongs to the TRAF family and is the key signaling protein in the NF-κB signaling pathways (Liu et al, 2012). TRAF6 could form a homodimer and catalyze K63-linked unbiquitination, which leads to the production of proinflammatory cytokines (Xu, Peng, et al, 2018). In addition, the ubiquitin-specific protease 4 could positively regulate retinoic acid-inducible gene I-like receptorinduced NF-κB activation by targeting TRAF6 for K48-linked deubiquitination and inhibit EV71 replication (Xu, Peng, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Xu et al demonstrated that upon enterovirus 71 (EV71) infections, USP4 expression was repressed, whereas the overexpression of USP4 suppressed EV71 replication. Hence, USP4 positively regulates NF-κB signaling by deubiquitinating K48-ubiquitin chains of TRAF6 in EV71 infection [74].…”
Section: Usp4mentioning
confidence: 98%